Rudeness in Expressing Criticism Towards Balinese Government’s Policies and Activities Found in Facebook’s Comments - Mulyana, Novita (International Seminar on Austronesian Languages and Literature, 2021)
This qualitative study is designed to identify (1) criticism expressed by people in giving comments on Facebook and (2) the type of rudeness contained in their utterances. The data used in this study were taken from Facebook’s comments sections. Due to the various topics and information shared on Facebook, the data taken were limited to utterances expressed by Facebook’s users in response to Balinese governments’ policies and activities which are related to Covid-19 pandemic. The data taken were analyzed based on Searle’s classification on types of illocutionary acts, especially expressive illocutionary act as well as Kasper’s classification of rudeness. The result of this study shows that motivated rudeness is the type of rudeness found in the way people expressed their criticism towards Balinese Government’s policies and activities which are related to Covid-19 pandemic.